The role of pyroptosis in endothelial dysfunction induced by diseases - Ju, Jin; Liu, Yanyan; Liang, Haihai; Yang, Baofeng (Frontiers in Immunology, 2023)
Most organs in the body rely on blood flow, and vesicular damage is the leading cause of injury in multiple organs. The endothelium, as the barriers of vessels, play a critical role in ensuring vascular homeostasis and angiogenesis. The past decade has seen the rapid development of risk factors in endothelial injuries, such as smoking, infectious, and diabetes mellites. Pyroptotic endothelium is an inflammatory mode of governed EC death that depend on the metabolic disorder and severe infectious such as atherosclerosis, and sepsis-related acute lung injury, respectively. Pyroptotic ECs need GSDMD cleaved into N- and C-terminal by caspase1, and the cytokines are released by a pore constructed by the N-terminal of GSDMD in the membrane of ECs, finally resulting in severe inflammation and pyroptotic cell death. This review will focus on the patho-physiological and pharmacological pathways of pyroptotic endothelial metabolism in diseases. Overall, this review indicates that pyroptosis is a significant risk factor in diseases and a potential drug target in related diseases.